Common genetic variants in pre-microRNAs are associated with cervical cancer susceptibility in southern Chinese women - Chen, Guange (J Cancer, 2020)
Cervical cancer is a commonly diagnosed cancer among females. Polymorphisms in pre-microRNAs have been demonstrated to play critical roles in cancer. However, the roles of pre-microRNA polymorphisms in the aetiology of cervical cancer have not been well documented. We genotyped eight pre-microRNA polymorphisms in 290 cervical cancer patients and 445 cancer-free female controls using quantitative polymerase chain reaction with TaqMan probes. To estimate the association between pre-microRNA polymorphisms and the risk of cervical cancer, an unconditional logistic regression model was used to calculate the odds ratio (OR) and 95% confidence interval (CI), adjusting for age, menopause, delivery, and abortion. We found that the pre-miR-137 rs1625579 T > G polymorphism was associated with a significant decrease in cervical cancer risk (TG/GG versus TT: adjusted OR (AOR) = 0.47, 95% CI = 0.27-0.81; TG versus TT: AOR = 0.56, 95% CI = 0.34-0.91). We also observed a significant association between the pre-miR-27a rs895819 T > C polymorphism and decreased cervical cancer risk (TC/CC versus TT: AOR = 0.65, 95% CI = 0.44-0.96). Stratified analysis further demonstrated that the pre-miR-137 rs1625579 T > C and pre-miR-27a rs895819 T > C polymorphisms significantly reduced the risk of cervical cancer susceptibility in patients younger than 49 years, those who experienced fewer abortions, and clinical stage I patients. Moreover, the pre-miR-137 rs1625579 T > G polymorphism showed protective effects in premenopausal women, squamous cell carcinoma patients, and patients with unclassified types of pathologies; the pre-miR-27a rs895819 T > C polymorphism was also associated with a decreased risk in patients older than 49 years, menopausal women, and women who had experienced vaginal pregnancies. The pre-miR-137 rs1625579 T > G and pre-miR-27a rs895819 T > C polymorphisms may provide protective effects against susceptibility to cervical cancer risk.